Challenges in the Development of Halal Certification System in Bangladesh: A Descriptive and Analytical Study based on Malaysian Experience - Aziz, Abu Hamid; Moniruzzaman (Halalsphere, 2022)
In the contemporary world, the Halal industry is seen as a fast-growing global business and it has become one of the most discussed matters around the world particularly in Muslim countries like Bangladesh. In the Halal industry, Halal certification has proven to be an important element in identifying the halal status of certain products or services and capturing global market shares and consumers. As the third-largest Muslim country (with 90% of Muslims) in the world, Bangladesh has huge potential in the Halal food industry. Yet, Bangladesh is far behind in terms of utilizing this potential due to several barriers and a very poor Halal certification system is one of them. On the other hand, Malaysia has made considerable use of its potential in the halal food industry through its well-known certification system worldwide due to its standardized procedures, requirements, and guidelines. This research paper aims to identify the challenges that cause a poor halal certification system and hinder its development in Bangladesh. A descriptive analysis shows how Malaysia has already overcome most of the challenges regarding Halal certification, and there are very few challenges that are on the way to be overcome. Finally, there are some suggestions that have been proposed by the authors to overcome the identified challenges in the development of the Halal certification system in Bangladesh, as well as to provide future research opportunities in the Halal industry in Bangladesh.